Generalisation of the Clark and Wells cognitive model of social anxiety to children's athletic and sporting situations. Issue 1 (1st January 2017) - Vassilopoulos, Stephanos P.; Brouzos, Andreas; Moberly, Nicholas J.; Tsorbatzoudis, Haralambos; Tziouma, Olga
ABSTRACT: Research has shown that social anxiety generalises to sporting and athletic situations. The present study explored the applicability of the Clark and Wells model of social anxiety – and its metacognitive extension – to sport anxiety. Participants were 290 students aged 11–13 years, who completed measures of sport anxiety, social anxiety, depression and cognitive variables implicated by the model. Hierarchical regression analysis indicated that performance attitudes, performance cognitions, anticipatory and post-event processing were predictive of sport anxiety, after controlling for social anxiety and depression. In addition, the association between performance attitudes and sport anxiety was stronger at higher levels of anticipatory and post-event processing. These results suggest that the Clark and Wells cognitive model – and its metacognitive extension – is applicable to children with sport anxiety.